2017
DOI: 10.1071/mf15391
|View full text |Cite
|
Sign up to set email alerts
|

Potential of submerged macrophytes to support food webs in lowland agricultural streams

Abstract: Submerged plants are often abundant in lowland streams in agricultural landscapes, but little is known of their role in stream ecosystems compared to riparian vegetation.We investigated the relative importance of submerged macrophytes as a basal resource of food webs in stream reaches with good and poor riparian vegetation condition, using mixing model analysis with stable carbon and nitrogen isotopes.Epilithic periphyton and terrestrial detritus were important basal resources in good condition reaches, althou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 62 publications
0
11
0
Order By: Relevance
“…Communities subject to a variety of both natural (Pringle & Hamazaki, ; Pusey, Arthington, Stewart‐Koster, Kennard, & Read, ; Reid, Lake, & Quinn, ) and anthropogenic (Cross et al., ; Layer, Hildrew, Monteith, & Woodward, ; Paice, Chambers, & Robson, ) disturbances show high levels of omnivory, which allows the community to persist in a variable environment. Pringle & Hamazaki () showed that removal of the omnivorous fish caused more variable dynamics in algal populations after severe storms, while Cross et al.…”
Section: Overview Of Omnivorymentioning
confidence: 99%
“…Communities subject to a variety of both natural (Pringle & Hamazaki, ; Pusey, Arthington, Stewart‐Koster, Kennard, & Read, ; Reid, Lake, & Quinn, ) and anthropogenic (Cross et al., ; Layer, Hildrew, Monteith, & Woodward, ; Paice, Chambers, & Robson, ) disturbances show high levels of omnivory, which allows the community to persist in a variable environment. Pringle & Hamazaki () showed that removal of the omnivorous fish caused more variable dynamics in algal populations after severe storms, while Cross et al.…”
Section: Overview Of Omnivorymentioning
confidence: 99%
“…SD and SEM values are exhibited in Supporting Information Table S4 opportunistic feeding were widespread (e.g. Blanchette et al, 2014;Paice et al, 2016). Furthermore, our study showed that dissimilarities among the diet of each taxon at each site were not explained by the availability of trophic resources.…”
Section: Discussionmentioning
confidence: 58%
“…Studies that combined different approaches such as stable isotope and gut content analyses also show considerable dietary variation within taxa among sites, and concluded that omnivory and opportunistic feeding were widespread (e.g. Blanchette et al., ; Paice et al., ). Furthermore, our study showed that dissimilarities among the diet of each taxon at each site were not explained by the availability of trophic resources.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In M+, Tanypus specimens could explore a higher percentage of animal items, which could be indicative of the trophic complexity found in this ecosystem. The presence of macrophytes in lakes can provide a great amount of resources to sustain complex food webs and long food chains (Ziegler et al ; Pace et al ). In contrast, in M−, Tanypus feeding was rather limited, with a greater affinity for Closterium , which was the only item consumed most of the time.…”
Section: Discussionmentioning
confidence: 99%